The clinical significance of serum complement component 1q tumor necrosis factor-related protein 3 and complement component 1q tumor necrosis factor-related protein 9 levels in patients with rheumatoid arthritis - Xin Li; Yuan Wang; Xiaoxia Jia; Jing Ke; Baoyu Zhang; Yan Wang (Wolters Kluwer Medknow Publications, 2022)
Objective: The objective of this study was to assess the expression of serum complement component 1q tumor necrosis factor-related protein 3 (CTRP3) and CTRP9 in rheumatoid arthritis (RA) patients, and further explore their correlation with disease activity and the predictive value of RA. Methods: RA group (n = 60) and healthy group (n = 60) were enrolled in Beijing Luhe Hospital, Capital Medical University. We collected the clinical data, including the basic information, laboratory parameters as well as the Disease Activity Score using 28 joint counts (DAS28) scores, and measured the expression of serum CTRP3 and CTRP9 in two groups by enzyme-linked immunosorbent assay. To analyze the correlation between serum CTRP3 and CTRP9 and RA. We explored the predictive value of the serum CTRP3 and CTRP9 for RA. Results: Compared to the healthy group, the expression of serum CTRP3 and CTRP9 was higher in the RA group (P < 0.05). Except rheumatoid factor (serum CTRP9: r = −0.310, P = 0.018), and immunoglobulin (serum CTRP9: r = 0.338, P = 0.010), platelet, erythrocyte sedimentation rate, C-reactive protein, DAS28, anti-cyclic citrullinated peptide antibody, triglyceride, total cholesterol, high-density lipoprotein, low-density lipoprotein, etc., of RA patients were not related to the levels of serum CTRP3 and CTRP9. The best cutoff value of serum CTRP3 and CTRP9 was 31.66 and 34.39 ng/ml, respectively. In terms of sensitivity, negative predictive value, and accuracy, compared with single detection of serum CTRP3 or CTRP9, combined detection has more predictive value for RA. Conclusion: CTRP3 and CTRP9 may become two candidate biomarkers for RA. The serum CTRP3 and CTRP9 may have certain predictive values for RA.